Effects of Web-Based Learning and F2F Learning on Teachers Achievement in Teacher Training Program in Indonesia - Wuryaningsih, Wuryaningsih; Susilastuti, Dewi Haryani; Darwin, Muhadjir; Pierewan, Adi Cilik (International Journal of Emerging Technologies in Learning (iJET), 2019)
Promoting the reform of teacher professional development (TPD) in the digital era using web-based learning (online and blended learning) appears to be a great innovation in improving teachers skills using technology through computers and Internet networks. Some research revealed that online learn-ing on TPD influences on improving teacher performance; however, the effect had no better results compared to traditional learning. Hence, this study evaluating the policy by examining the effects of web-based learning model, i.e., online and blended learning, and face to face approach on the scores achieved in teacher training. The study adopted the quasi-experimental design with pre-post non-equivalent group design of the intact teacher training program. The participants were 427,189 teachers covering all school levels in Indonesia. Findings suggest that the web-based learning model is more effective in teacher achievement than the f2f, while the female tends to be better than male. Hence, digital constraint is not an obstacle for the teacher in the web-based model. Interestingly, blended learning that emerged as a new trend in e-learning proved to be quite promising. These findings provide considerations for the development of a policy for an appropriate TPD model for teachers at different levels.